Kata Kerja Akar Pembentuk Kata Derivasi dalam Bahasa Jepang: Verbs as Root Words Forming Derivatives in Japanese - Adrianis Adrianis; Dhian Asri; Diah Noverita (Universitas Tidar, 2025)
This article examines the formation of derivative words in Japanese with verb roots found in Japanese textbooks and dictionaries. Derivation is a word formation process that can change the identity of words from their basic form. This research on verbs as roots forming derivative words in Japanese uses a descriptive qualitative method. Data collection was conducted using the observation method, with tapping and note-taking techniques. Analysis was performed using translational matching and referential matching methods. The presentation of data analysis results uses an informal method. The research results on verb roots forming derivatives in Japanese indicate that derivative formation causes morphological, syntactic, and semantic processes. Derivative formations undergoing morphological processes include the deletion of the letters